Authenticity of Traditional Houses, Islam and Cultural Tourism Products and Services - Baharudin Baharudin; Muhammad Adi Junaidi; Lalu Muhammad Ariadi (Ulumuna, 2023)
This study aims to explore the role of Islam on the morphological authenticity of house buildings in the indigenous people of Limbungan Perigi Village, Lombok Timur and its relationship with the existence of cultural tourism. The ethnographic method summarised qualitative data through in-depth interviews and participatory observations for four months at the research site. Data analysis is sourced from primary data in the form of contact persons who know the identity of the data studied (elders, traditional leaders and indigenous youth) who have settled permanently. Research samples are taken purposively for data representation that must be valid and provide accurate and factual information. Secondary data in the form of literature references are also material for improving this research. The results showed a close relationship between Islam, the traditional house of the Limbungan community and the positioning of cultural tourism by the local government. The traditional house of the Sasak tribe of Limbungan Perigi has Islamic architectural values such as Bale (houses), roofs, walls, doors, floors, foundations, stairs, barns, and others. This value contains aesthetics, holistic education, manners, and social, cultural and economic values. Customs, traditions and Islam in the indigenous people of Limbungan Perigi are the subjects of a comprehensive study in this research.